Tinjauan Hukum Kerahasiaan Rekam Medis dalam Laporan Kesehatan Ibu dan Anak Berbasis Digital - Elizabet Catherine Jusuf; Ria Kumala; Adriano Adriano (Universitas Batanghari Jambi, 2023)
The study aims to explain about legal aspects of medical record data confidentiality in digitally based maternal and child health reports. Teh method of this study is normative legal research with a conceptual approach, then quantitative analysis of legal interpretation. This Study shows confidentiality of information about patients is addressed to all health workers, administrative personnel (not health workers) who have access, and students or students who are obtaining education in every health service facility, both data information stored manually and digitally. The dissemination of personal data without permission is a criminal act and violates the code of ethics. Maintaining the confidentiality of digital-based maternal and child health report data is an obligation for all health workers and administrative personnel who have access to or are involved in this activity and this is protected by the Law but it has not have the specific rule.